The History of Islamic Civilization in the Digital Age: Challenges and Opportunities for Gen Z - An An Siti Nurhasanah; Lina Pusvitasari; Fani Deskia Fitri Ramadhan; Rini Pasini (Penerbit Hellow Pustaka, 2025)
Islamic civilization in the digital era faces significant challenges and opportunities, especially for Generation Z. Digitalization has changed the way Muslims interact with religious teachings, facilitating access to information but also increasing the risk of distorting Islamic values. Generation Z, who are tech-savvy, intend to become agents of change by utilizing social media to spread Islamic values ​​and innovate in religious education. However, they also have to face challenges, such as hoaxes and secularism that can erode Islamic identity. In its development, currently, the value system of Islamic civilization is starting to erode.including in Indonesia. This is due to various factors, one of which is the development in the digital era. The development of digital technology has had a significant impact on civilization, Islam in Indonesia. The digital era has presented complex challenges in maintaining and strengthening the role of Islam in society. Habits (culture) that are not in accordance with their beliefs. In this discussion, the aim is to provide an overview of the challenges in the digital era, especially the internet, Towards civilization, Islam in Indonesia and offers alternatives on how technology can be used to strengthen Islamic civilization. Technology can have a positive impact on Islamic society in Indonesia if it is based on Islamic principles.